Bagi Hasil Tanah Pertanian yang dibebani Hak Gadai dalam Budaya Pertanian Masyarakat - Heryanti . (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2013)
ABSTRACT The objective of this writing is to know the shared-income system for agricultural land that is encumbered pawning right on the culture of farming community. The type of research is a normative study. Types and sources of data are secondary data with the data collection and literature methods. Data were analyzed by descriptive qualitative. The resume of this writing is that the shared-outcome system for agricultural land that was encumbered pawning right on the culture of farming community that the shared-outcome of the agricultural land was done through some form of agreement between a person entitled to a field of agricultural land from others who called cultivators, by appointment where cultivators were allowed to cultivate the concerned land and the outcome of operation of the land would be divided according to agreement which had been agreed upon, which was usually the a half shared-outcome for cultivators and a half for land owners. Key words: land shared-income, pawning right